(untitled) (Bangladesh Journal of Medicine, 2021)
Hematochezia or passage of fresh blood per rectum is a relatively common finding in medical practice which mostly indicates lower gastrointestinal bleeding. The causes for lower gastrointestinal bleeding include diverticular disease, vascular ectasia, ischemic, inflammatory or infectious colitis, colonic neoplasia, hemorrhoids, anal fissures and small bowel lesions (Crohn’s disease, Vascularectasia, Meckel’s diverticulum).If a patient comes with severe hematochezia, the first and foremost task is to stabilize the patient and then find out the source of bleeding as soon as possible. Elderly patients presenting with severe hematochezia, is most likely due to colorectal malignancy but benign causes like colonic diverticulosis can also present as life threatening bleeding in rare occasions. Here we report a case of 70-years-old male patient presenting with severe painless hematochezia leading to severe anemia due to diverticulosis. Bangladesh J Medicine July 2022; 33(1) : 94-98